Interprofessional Simulation and Education: Physical Therapy, Nursing, and Theatre Faculty Work Together to Develop a Standardized Patient Program. Issue 6 (November 2015) - Swift, Marcie C.; Stosberg, Tobey
Abstract : N/A: A well‐conceived training program for standardized patients (SPs) can increase their effectiveness in portraying actual patients. This article describes the development of an SP program that allows graduate and undergraduate students to engage in interprofessional experiences in a multifunctional simulation center. Three academic programs at a midwestern university developed an interdisciplinary course that trains undergraduate students as SPs for nursing and physical therapy simulation experiences. The SP program has opened doors for interprofessional collaboration beyond current simulation experiences and has exposed the university community to simulation.